A plant-based meal affects thalamus perfusion differently than an energy- and macronutrient-matched conventional meal in men with type 2 diabetes, overweight/obese, and healthy men: A three-group randomized crossover study. Issue 4 (April 2021) - Kahleova, Hana; Tintera, Jaroslav; Thieme, Lenka; Veleba, Jiri; Klementova, Marta; Kudlackova, Michaela; Malinska, Hana; Oliyarnyk, Olena; Markova, Irena; Haluzik, Martin; Pavlovicova, Renata; Hill, Martin; et al.
Summary: Background & aims: Reward circuitry in the brain plays a key role in weight regulation. We tested the effects of a plant-based meal on these brain regions. Methods: A randomized crossover design was used to test the effects of two energy- and macronutrient-matched meals: a vegan (V-meal) and a conventional meat (M-meal) on brain activity, gastrointestinal hormones, and satiety in participants with type 2 diabetes (T2D; n = 20), overweight/obese participants (O; n = 20), and healthy controls (H; n = 20). Brain perfusion was measured, using arterial spin labeling functional brain imaging; satiety was assessed using a visual analogue scale; and plasma concentrations of gut hormones were determined at 0 and 180 min. Repeated-measures ANOVA was used for statistical analysis. Bonferroni correction for multiple comparisons was applied. The Hedge's g statistic was used to measure the effect size for means of paired difference between the times (180-0 min) and meal types (M−V meal) for each group. Results: Thalamus perfusion was the highest in patients with T2D and the lowest in overweight/obese individuals (p = 0.001). Thalamus perfusion decreased significantly after ingestion of the M-meal in men with T2D (p = 0.04) and overweight/obese men (p = 0.004), and it decreased significantly after ingestion of the V-meal in healthy controls (p < 0.001; Group x Meal x Time: F = 3.4; p = 0.035). The effect size was −0.41 (95% CI, −1.14 to 0.31; p = 0.26) for men with diabetes; −0.72 (95% CI, −1.48 to 0.01; p = 0.05) for overweight/obese men; and 0.82 (95% CI, 0.09 to 1.59; p = 0.03) for healthy men. Postprandial secretion of active GLP-1 increased after the V-meal compared with the M-meal by 42% (95% CI 25–62%; p = 0.003) in men with T2D and by 41% (95% CI 24–61%; p = 0.002) in healthy controls. Changes in thalamus perfusion after ingestion of both test meals correlated with changes in satiety (r = +0.68; p < 0.01), fasting plasma insulin (r = +0.40; p < 0.01), C-peptide (r = +0.48; p < 0.01) and amylin (r = +0.55; p < 0.01), and insulin secretion at 5 mmol/l (r = +0.77; p < 0.05). Conclusions: The higher postprandial GLP-1 secretion after the V-meal in men with T2D, with concomitant greater satiety and changes in thalamus perfusion, suggest a potential use of plant-based meals in addressing the key pathophysiologic mechanisms of food intake regulation. Trial registration ClinicalTrials.gov number, NCT02474147 .